Governors and directors: Competing models of corporate governance. (August 2019) - Shah, Neeta; Napier, Christopher J
Why do we use the term 'corporate governance ' rather than 'corporate direction '? Early British joint stock companies were normally managed by a single 'governor'. The 'court of governors' or 'board of directors' emerged slowly as the ruling body for companies. By the nineteenth century, however, companies were typically run by directors while not-for-profit entities such as hospitals, schools and charitable bodies had governors. The nineteenth century saw steady refinement of the roles of company directors, often in response to corporate scandals, with a gradual change from the notion of the director as a 'representative shareholder' to the directors being seen collectively as 'representatives of the shareholders'. Governors in not-for-profit entities, however, were regarded as having broader responsibilities. The term 'governance' itself suggests that corporate boards should be studied as 'political' entities rather than merely through economic lenses such as agency theory.